1991
DOI: 10.1128/jb.173.23.7519-7524.1991
|View full text |Cite
|
Sign up to set email alerts
|

Location and cloning of the ketal pyruvate transferase gene of Xanthomonas campestris

Abstract: Genes required for xanthan polysaccharide synthesis (xps) are clustered in a DNA region of 13.5 kb in the chromosome of Xanthomonas campestris. Plasmid pCHC3 containing a 12.4-kb insert of xps genes has been suggested to include a gene involved in the pyruvylation of xanthan gum (N.E. Harding, J.M. Cleary, D.K. Cabañas, I. G. Rosen, and K. S. Kang, J. Bacteriol. 169:2854-2861, 1987). An essential step toward understanding the biosynthesis of xanthan gum and to enable genetic manipulation of xanthan structure i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
23
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(24 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…Preparation of EDTA-treated cells and the assay for in vitro synthesis of xanthan gum were done as previously described (Ielpi et al, 1981a), but using UDP-['4C]GlcA as radiolabelled sugar, and unlabelled UDP-Glc and GDP-Man as sugar donors (Marzocca et al, 1991). Under these conditions, in incubations done with EDTA-treated wild-type cells, the main product extracted in the lipid fraction is ['4C-GlcA]ps-P-P-lipid, but small amounts of a [14C-GalAIlipid-bound galacturonide, which is also formed, may be present (Baldessari et al, 1990).…”
Section: Methodsmentioning
confidence: 99%
“…Preparation of EDTA-treated cells and the assay for in vitro synthesis of xanthan gum were done as previously described (Ielpi et al, 1981a), but using UDP-['4C]GlcA as radiolabelled sugar, and unlabelled UDP-Glc and GDP-Man as sugar donors (Marzocca et al, 1991). Under these conditions, in incubations done with EDTA-treated wild-type cells, the main product extracted in the lipid fraction is ['4C-GlcA]ps-P-P-lipid, but small amounts of a [14C-GalAIlipid-bound galacturonide, which is also formed, may be present (Baldessari et al, 1990).…”
Section: Methodsmentioning
confidence: 99%
“…It has been suggested that the EPS may play a role in the ability of Xanthomonas spp. to infect plants (58) have induced mutations affecting its EPS (2,6,26,28,33,38,60,65) and no definitive role of its EPS or cell surface molecules in virulence has been determined (2,9,17,29,36,44,48,59,61). Defects in the LPS of Rhizobium, Erwinia, and Pseudomonas species can lead to partial or complete loss of virulence (30,43,51).…”
Section: M28mentioning
confidence: 99%
“…The opsXY locus affected the EPS of 3048 but was not observed to complement any of the 90 non-or low-mucoid mutants of X. campestris tested in the Kelco, Inc., collection. The mutational lesions in these 90 mutants were mapped to eight different regions of the chromosome and are involved in the synthesis of the pentasaccharide (26), synthesis of the sugar nucleotide precursors (38), or to unknown functions of xanthan biosynthesis (25a). These results indicated that the opsXY locus was not primarily involved in EPS biosynthesis.…”
Section: Gca Cgc Gcg CM Tgg Gac Gac Gat Ggc Cgc Cct Gta Ctg Atg Atc Tmentioning
confidence: 99%
“…(19,20), Rhizobium sp. (21,22), and Bacillus anthracis (23), among other species, it was of interest to determine whether S. pombe has a genome-encoded functional analog of these proteins.…”
mentioning
confidence: 99%